Outcomes of splenectomy in patients with common variable immunodeficiency (CVID): a survey of 45 patients - Wong, G K (Blackwell Science Inc, 2013)
Splenectomy has been used in patients with common variable immunodeficiency disorders (CVID), mainly in the context of refractory autoimmune cytopenia and suspected lymphoma, but there are understandable concerns about the potential of compounding an existing immunodeficiency. With increasing use of rituximab as an alternative treatment for refractory autoimmune cytopenia, the role of splenectomy in CVID needs to be re-examined. This retrospective study provides the largest cohesive data set to date describing the outcome of splenectomy in 45 CVID patients in the past 40 years. Splenectomy proved to be an effective long-term treatment in 75% of CVID patients with autoimmune cytopenia, even in some cases when rituximab had failed. Splenectomy does not worsen mortality in CVID and adequate immunoglobulin replacement therapy appears to play a protective role in overwhelming post-splenectomy infections. Future trials comparing the effectiveness and safety of rituximab and splenectomy are needed to provide clearer guidance on the second-line management of autoimmune cytopenia in CVID.